Stability of spinal bone lesions in patients with multiple myeloma after radiotherapy - a retrospective analysis of 130 cases - Uzun-Lang, Kristin; König, Laila; Bruckner, Thomas; Förster, Robert; Sprave, Tetyana; Schlampp, Ingmar; Bostel, Tilman; Welte, Stefan Ezechiel; Nicolay, Nils; Debus, Jürgen; Rief, Harald (Clinical lymphoma, myeloma & leukemia, 2017)
Background: The objective of the present retrospective analysis was the response evaluation regarding bone density and stability of patients with osteolytic spinal bone lesions due to multiple myeloma after palliative radiotherapy (RT). Patients and Methods: Patients with multiple myeloma who had undergone spinal RT from March 2003 to May 2016 were analyzed before and 3 and 6 months after RT. Assessment of spinal stability and bone density was performed using the internationally recognized Taneichi scoring system and measurement of bone density using computed tomography imaging-based Hounsfield units. For statistical analysis, we used the Bowker test, McNemar test, and κ statistics to detect possible asymmetries in the distribution of the Taneichi score over time. We used the Student t test for comparison of the density values (Hounsfield units) before and after treatment. Toxicity was evaluated using the Common Terminology Criteria for Adverse Events, version 4.0. Additionally, overall survival was calculated using the Kaplan-Meier method. Results: We evaluated 130 patients (69% male; 31% female) with multiple myeloma and a median age of 58 years. The median follow-up period was 41 months. Before treatment, 51% of the lesions were classified as unstable. At 3 and 6 months after RT, this rate had decreased to 41% (P = .0047) and 24% (P = .2393), respectively. The computed tomography measurements showed a significant increase in bone density at 3 and 6 months after RT. Acute RT-related grade 1 and 2 complications were detected in 34% of patients. Late side effects (grade 1-2) were detected in 23% of the patients. No severe grade 3 or 4 acute or late toxicities were identified. The median overall survival was 19.7 months for all patients and 6.6 months for patients with a Karnofsky performance score of ≤ 70%. Conclusion: To the best of our knowledge, ours is the first report to analyze the bone density and stability in patients with multiple myeloma after RT using a validated scoring system and computed tomography imaging. Palliative RT is an effective method resulting in a significant increase in bone density for local response and stability without severe RT-related toxicity. Furthermore, recalcification could already be detected at 3 months after treatment.
Gesehen am 15.10.2018